MENINGKATKAN KEMAMPUAN MEMBACA NYARING DENGAN MENGGUNAKAN TEKS CERITA RAKYAT (BATU MENANGIS)DALAM MATA PELAJARAN BAHASA INDONESIA PADASISWA KELAS IV SD INPRES ALOR KECIL II - Goga, Intan; Lapung, Jamra (Jurnal Edukasi, 2025)
This research use classroom action research method. The formulations of the problem in this study are : How is the process of learning to read aloud by using folklore text in IV grade students of SD Inpres Alor Kecil II? and what is the result of the ability to read using folklore text in grade IV students of SD Inpres Alor Kecil II?. The purpose of this study is : To find out the process of learning to read aloud by using folklore text in grade IV students of SD Inpres Alor Kecil II and to find out the results of the ability of reading aloud by using folklore text in IV grade students of SD Inpres Alor Kecil II with the subject of research totaling 12 students consisting of 4 male students and 8 female students. In each cycle the data collection techniques that used in the study are data about the learning outcomes of the test reading students. The result of this study indicate that there is an increase in the ability to read aloud students. By using folklore text, it can increase the average value of reading result students in SD Inpres Alor Kecil II from cycle 1 to 72,08 while cycle 2 it has increased to 77,08. Basides that, the observation data from each cycle start from the teacher’s observation data to the observation data changes from each activity during the learning process in class. From the results of the analysis it can be concluded that through text folklore can improve the ability to read aloud students of IV grade in SD Inpres Alor Kecil II.